Uncle Murad's story "Stars burn forever" and conclusions from his psycholinguistic analysis - Buronova Rano Abdujabborovna; Abdullayev Islom Yunus o‘g’li; Muxiddinova Muhlisa Shamsiddin qizi (Zien Journals, 2022)
At a time when many new fields of linguistics are emerging, we are witnessing a slight decline in psycholinguistic analysis. The study of the human psyche in comparison with the means of language and speech is a bit complicated. Although it is enough for the interpretation and analysis of a work of art, we see a lack of research.” Psycholinguistic interpretation of the story and the conclusions drawn from it.
Keywords: psycholinguistic; Linguistics; lingvopoetic